Branding on Social Media Platforms As a Solution For Mixed Procession Music Groups In The City Of Padang, West Sumatra, Indonesia - HR, Hafif; Marh, Fahmi; Rosa, Della; Surayya, Yade (LPPM Institut Seni Indonesia Padangpanjang, 2023)
Pancaragam, the only active music group in West Sumatra Province, Indonesia, holds significant potential but has yet to gain widespread recognition. Similar to Tanjidor groups in Betawi Kalimantan, such as Pontianak and Pemangkat, Pancaragam faces challenges in expanding its reach and economic impact on its musicians. To address this, we offer strategic solutions focused on enhancing visibility through social media platforms. This proposal includes the implementation of management patterns that align with the characteristics of each social media platform. Firstly, a profound understanding is needed on how to manage and leverage the specific features of platforms such as Instagram, Facebook, and YouTube. This involves the use of compelling visual content, such as video snippets from their performances, as well as active engagement with fans through comments and direct messaging. Furthermore, the implementation of creative digital campaign strategies can elevate Pancaragam's online presence. Contests or music challenges on these platforms can encourage community participation, while special offers or discounts for live performances can attract a broader audience. Collaborating with local influencers or social media users with an interest in traditional arts and culture can also be an effective way to expand networks and reach new audiences. With a combination of focused management and digital marketing strategies, Pancaragam can gain broader recognition, enhance their online presence, and ultimately provide a positive economic impact for its musicians.